Isolation of Specific Small‐Diameter Single‐Wall Carbon Nanotube Species via Aqueous Two‐Phase Extraction. (21st January 2014) - Fagan, Jeffrey A.; Khripin, Constantine Y.; Silvera Batista, Carlos A.; Simpson, Jeffrey R.; Hároz, Erik H.; Hight Walker, Angela R.; Zheng, Ming
<x xml:space="preserve">Abstract</x> Aqueous two‐phase extraction is demonstrated to enable isolation of single semiconducting and metallic single‐wall carbon nanotube species from a synthetic mixture. The separation is rapid and robust, with remarkable tunability via modification of the surfactant environment set for the separation. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>